MACB CKD Task Force updated recommendations for reporting estimated glomerular filtration rate and albuminuria in adults - Chellappah Thambiah, Subashini; Sthaneshwar, Pavai; Leslie, Charles Lai; Soo, Kun Lim; Zulkely, Ahmad; Low, Yoke Lee; Mohamad Noor, Nafisah; Peck, Ham Chuo; Ishak, Sazaliah; Anas, Siti Sharina; Abdullah Soheimi, Siti Suhana; Raja Aziddin, Raja Elina (Malaysian Society of Pathologists, 2024)
Chronic kidney disease (CKD) is a common clinical condition with significant health risks for patients and is widely recognised as a major public health concern. Laboratory medicine plays a crucial role in both diagnosing and managing CKD, as diagnosis and staging rely on estimated glomerular filtration rate (GFR) and evaluating albuminuria (or proteinuria). It was evident that the laboratory assessment of CKD in Malaysia is not standardised. In light of this, the Malaysian Association of Clinical Biochemistry CKD (MACB-CKD) Task Force issued a national recommendation for laboratory diagnosis of CKD in 2019. Recently, Kidney Disease: Improving Global Outcomes (KDIGO) updated its recommendations for the diagnosis, evaluation, management, and treatment of CKD. These guidelines incorporate the most recent evidence-based practices to support laboratory professionals in delivering optimal care for individuals with CKD, focusing on critical areas such as estimated GFR (eGFR), albuminuria assessment, and risk stratification. The latest National Institute for Health and Care Excellence (NICE) guidelines on CKD has also incorporated the Kidney Failure Risk Equation (KFRE) as a tool for predicting the likelihood of progression to end-stage kidney disease (ESKD) in CKD patients. Hence, the MACB-CKD Task Force has reviewed and updated its recommendations for laboratory reporting of eGFR and urine albumin in alignment with the latest guidelines.